Rice fields are considered to be among the highest sources of atmospheric methane, an important source of global warming. In order to meet the projected rice needs of the increasing world population, it is estimated that the annual world's rough rice production must increase to 760 million tons (a 65% increase) in the next 30 years. This will increase methane emissions from rice fields if current technologies are kept (Minami and Neue, 1993). Indonesia, a country of which rice is one of its - Arief Sabdo Yuwono (Jurnal Keteknikan Pertanian, 1998)
Rice fields are considered to be among the highest sources of atmospheric methane, an important source of global warming. In order to meet the projected rice needs of the increasing world population, it is estimated that the annual world's rough rice production must increase to 760 million tons (a 65% increase) in the next 30 years. This will increase methane emissions from rice fields if current technologies are kept (Minami and Neue, 1993). Indonesia, a country of which rice is one of its staple foods, produces 43.2 M tons of rice per year (Indonesia's Central Bureau of Statistics, 1992). It is produced from wetland paddy of 9.2 M ha and 1.2 M ha dry land paddy.